Clifford's spring clean-up - Bridwell, Norman (New York, 1997)
An all-new Clifford adventure finds the big red dog hard at work getting the house clean, or trying to, as he shakes to pieces Emily Elizabeth's rugs and digs up weeds at a vacant lot for Earth Day. Original.